Phenomenographies: describing the plurality of atmospheric worlds - Federico De Matteis; Mikkel Bille; Tonino Griffero; Andrea Jelić (Ambiances)
In recent years, the theory of atmospheres has extended beyond phenomenology and aesthetics, informing a wide variety of descriptive practices in the humanities. Diverse scholarly fields such as anthropology and architecture, musicology and art criticism now include the notion of atmospheric space in their methodological toolkits. The descriptive practices of lived space, however, entail several theoretical questions, concerning the potential and limits of giving voice to first-person experience. In the introductory essay of the 2019 special issue of Ambiances, we address the methodological perspectives emerging from the articles and discuss several question concerning the theory of atmospheres and the practices aimed at describing them.